An Online Calibration and Detection Method for Inertial Equipment on Aircraft. (June 2020) - Song, W Y; Wu, X H; Wang, J; Sun, Y G; Fang, Y
Abstract: At present, the calibration and detection for inertial equipment on aircraft generally need to disassemble the inertial equipment from the aircraft, and it is inconvenient to use this method to maintain the inertial equipment. An online calibration and detection method is proposed in the paper, which is able to obtain the detection indexes by combining the vertical and rotary motion of the launching vehicle. The indexes contain the zero drift indexes, the scale factor nonlinear indexes and the attitude angle error indexes of the gyro and accelerometer. By judging if these indexes are within the threshold range of requirements, we can determine whether the inertial equipment perform well. Using the designed limit index as the calibration parameter, the simulation experiment of shooting is carried out to verify the effectiveness of the designed method. The simulation results show that the miss distance meets the design requirements within the limit index range. The designed algorithm can directly detect the inertial equipment online, avoiding the repeated disassembly and assembly problems caused by the traditional detection methods, and reducing the test and maintenance costs.